Association of CRP genetic variants with blood concentrations of C‐reactive protein and colorectal cancer risk. Issue 5 (28th July 2014) - Nimptsch, Katharina; Aleksandrova, Krasimira; Boeing, Heiner; Janke, Jürgen; Lee, Young‐Ae; Jenab, Mazda; Bueno‐de‐Mesquita, H.B(as); Jansen, Eugène HJM; Tsilidis, Konstantinos K; Trichopoulou, Antonia; Weiderpass, Elisabete; Wu, Chunsen; et al.
<x xml:space="preserve">Abstract</x> High blood concentrations of C‐reactive protein (CRP) have been associated with elevated risk of colorectal cancer in several prospective studies including the European Prospective Investigation into Cancer and Nutrition (EPIC), but it is unknown whether these observations reflect a causal relationship. We aimed to investigate whether CRP genetic variants associated with lifelong higher CRP concentrations translate into higher colorectal cancer risk. We conducted a prospective nested case–control study within EPIC including 727 cases diagnosed between 1992 and 2003 and 727 matched controls selected according to an incidence‐density sampling protocol. Baseline CRP concentrations were measured in plasma samples by a high sensitivity assay. Tagging single nucleotide polymorphisms (SNPs) in the CRP gene (rs1205, rs1800947, rs1130864, rs2808630, rs3093077) were identified via HapMap. The causal effect of CRP on colorectal cancer risk was examined in a Mendelian Randomization approach utilizing multiple CRP genetic variants as instrumental variables. The SNPs rs1205, rs1800947, rs1130864 and rs3093077 were significantly associated with CRP concentrations and were incorporated in a CRP allele score which was associated with 13% higher CRP concentrations per allele count (95% confidence interval 8–19%). Using the CRP‐score as instrumental variable, genetically twofold higher CRP concentrations were associated with higher risk of colorectal cancer (odds ratio 1.74, 95% confidence interval 1.06–2.85). Similar observations were made using alternative definitions of instrumental variables. Our findings give support to the hypothesis that elevated circulating CRP may play a direct role in the etiology of colorectal cancer.